Size-dependent response of foraminiferal calcification to seawater carbonate chemistry - Henehan, Michael J.; Evans, David; Shankle, Madison; Burke, Janet E.; Foster, Gavin L.; Anagnostou, Eleni; Chalk, Thomas B.; Stewart, Joseph A.; Alt, Claudia H. S.; Durrant, Joseph; Hull, Pincelli M. (Biogeosciences, 2017)
Michael J. Henehan acknowledges financial support from the Yale Peabody Museum. The response of the marine carbon cycle to changes in atmospheric CO2 concentrations will be determined, in part, by the relative response of calcifying and non-calcifying organisms to global change. Planktonic foraminifera are responsible for a quarter or more of global carbonate production, therefore understanding the sensitivity of calcification in these organisms to environmental change is critical. Despite this, there remains little consensus as to whether, or to what extent, chemical and physical factors affect foraminiferal calcification. To address this, we directly test the effect of multiple controls on calcification in culture experiments and core-top measurements of Globigerinoides ruber. We find that two factors, body size and the carbonate system, strongly influence calcification intensity in life, but that exposure to corrosive bottom waters can overprint this signal post mortem. Using a simple model for the addition of calcite through ontogeny, we show that variable body size between and within datasets could complicate studies that examine environmental controls on foraminiferal shell weight. In addition, we suggest that size could ultimately play a role in determining whether calcification will increase or decrease with acidification. Our models highlight that knowledge of the specific morphological and physiological mechanisms driving ontogenetic change in calcification in different species will be critical in predicting the of foraminiferal calcification to future change in atmospheric pCO2. Peer reviewed